Case-crossover study to examine the change in postpartum risk of pulmonary embolism over time - Grégoire Ficheur; Alexandre Caron; Jean-Baptiste Beuscart; Laurie Ferret; Yu-Jin Jung; Charles Garabedian; Régis Beuscart; Emmanuel Chazard (BMC, 2017)
Abstract Background Although the current guidelines recommend anticoagulation up until 6 weeks after delivery in women at high risk of venous thromboembolism (VTE), the risk of VTE may extend beyond 6 weeks. Our objective was to estimate the risk of a pulmonary embolism in successive 2-week intervals during the postpartum period. Methods In a population-based, case-crossover study, we analyzed the French national inpatient database from 2007 to 2013 (n = 5,517,680 singleton deliveries). Using ICD-10 codes, we identified women who were diagnosed with a postpartum pulmonary embolism between July 1st, 2008, and December 31st, 2013. Deliveries were identified during a case "period" immediately before the pulmonary embolism, and five different control periods one year before the pulmonary embolism. Using conditional logistic regression, Odds ratios (ORs) and 95% confidential intervals (CIs) were estimated for ten successive 2-week intervals that preceded the diagnosis of pulmonary embolism. Results We identified 167,103 cases with a pulmonary embolism during the inclusion period. After delivery, the risk of pulmonary embolism declined progressively over time, with an OR [95%CI] of 17.2 [14.0-21.3] in postpartum weeks 1 to 2 and 1.9 [1.4-2.7] in postpartum weeks 11 to 12. The OR [95%CI] in postpartum weeks 13 to 14 was 1.4 [0.9-2.0], and the OR did not fall significantly after postpartum week 14. Conclusions Our findings indicate that women are at risk of a pulmonary embolism up to 12 weeks after delivery. The shape of the risk curve suggests that the risk decreases exponentially over time. Future research is needed to establish whether the duration of postpartum anticoagulation should be extended beyond 6 weeks.